An evaluation of machine operator exposure to occupational noise during harvesting and extraction operations in Brazilian eucalyptus plantations - Camargo, Diego Aparecido [UNESP]; Munis, Rafaele Almeida [UNESP]; Miyajima, Ricardo Hideaki [UNESP]; Andrade Lima, Roldao Carlos [UNESP]; Simoes, Danilo [UNESP] (Taylor & Francis Inc, 2022)
Wood harvesting operations involve mechanized and semi-mechanized machines that expose operators to occupational noise. It was verified that the emission of occupational noise levels in the harvest of mechanized and semi-mechanized wood in Brazilian forests planted with eucalyptus were in compliance with Directive 2003/10/EC. Noise data were collected using two personal-use integrative meters. The lower action level of 80 dB(A), the upper action level of 85 dB(A) and the exposure limit of 87 dB(A) were evaluated. The results showed that 16.6% of the operators were exposed to thresholds above the lower action level, but remained below the upper level of 85 dB(A), 8.3% of the operators were exposed to occupational noise levels above the upper action level, without exceeding the exposure limit of 87 dB(A) and 25% of operators were exposed to levels above the exposure limit. Therefore, the occupational noise levels achieved when harvesting mechanized and semi-mechanized wood in forests planted with eucalyptus do not comply with Directive 2003/10/EC.
Keywords: Forest operations; Hearing system; Occupational Safety; Physical agents